Determination of in vitro antioxidant activities and phenolic compounds of different extracts of Salvia verticillata ssp. verticillata and spp. Amasiaca from Turkey's flora - Onder YUMRUTAS, Atalay SOKMEN, Nilgun OZTURK (Journal of Applied Pharmaceutical Science)
This study was designed to evaluate the in vitro antioxidant activities of hexane,dichloromethane and methanol extracts of Salvia verticillata ssp. verticillata and spp. amasiaca.The samples were subjected to screening for their possible antioxidant activity by using 2,2-diphenyl-1-picriylhydrazyl (DPPH) and β-carotene/linoleic acid assays. The methanol extractsparticularly found to posses strong antioxidant activities (IC50= 16.0 ± 3.01 and 12.1 ± 3.82 mgml-1, respectively) whereas the dichloromethane extracts showed low activities. In the linoleicacid system, oxidation of the linoleic acid was moderately inhibited by the methanol extracts(61.3 ± 5.38 and 68.7 ± 1.82 %, respectively). Also, in methanol extracts of these plants havebeen determined amount of 9 phenolic compounds in different proportions and identified by theRP-HPLC method. These plants have high level of rosmarinic acid (37.1 and 24.83 mg/g,respectively) when compared with other components. Amounts of caffeic acid were determinedas 9.82 and 8.69 mg/g, respectively. Our results showed that the high levels of rosmarinic andcaffeic acid are more likely to be responsible for most of the observed antioxidant activities ofSalvia species.
Keywords: Salvia verticillata ssp. verticillata, Salvia verticillata spp. amasiaca, Antioxidant activity, Phenolic contents,DPPH,HPLC.